Deliver : the untaught lessons to growth hack your career - Lin, Wen-Szu (Mandaluyong City : Anvil Publishing, Inc., 2021)
Deliver. is a structured set of learning told through engaging stories from my experiences and from the voices of others. The lessons follow the concept of inside-out. The focus is on how to develop the self into a great individual contributor at work, through lessons on how to think in a structured manner, how to communicate, and how to manage one$1 (Bs emotions. The lessons then expand outwards to teach a person how to build and manage relationships, both as a stakeholder and as a manager. It ends with insights on how to become a great leader.s
Keywords: Business Communication; Personal growth; Business and economics